Wildlife of Australia - Campbell, Iain, 1969- (Princeton pocket guides., 2013)
This photographic pocket guide covers the most widely seen birds, mammals, reptiles, amphibians, and habitats of Australia, featuring more than 400 stunning color photographs, and coverage of 350 birds, 70 mammals, 30 reptiles, and 16 frogs likely to be encountered in Australia's major tourist destinations.